Strategies for using online health communities by elderly people in rural areas - K. A. Galkin (Цифровая социология)
The article considers the older people integration into online health communities. The author explored the role of such communities in constructing new types of sociality between older people, where online communities become intermediary actors structuring and changing the usual practices of everyday life and setting special context for older people’s communication. This study contributes to the study of the possibilities and limitations of online communities use in the context of the of older people lives with chronic illnesses in rural areas. For the people in focus, these communities can make up for the lack of communication often experienced by people who live in areas remote from major population centers and health centers. The importance of online communities is determined by the fact that it is often difficult for an older person in peripheral settlements to get the necessary advice or recommendation from a doctor, and communication in online health communities and medical forums compensates for this deficit, which is important in the treatment of the disease. Based on a study of groups of older people participating in online forums, different strategies for using online communities have been typified. In particular, three strategies have been identified: communication, using and observation. For each of them, the features of the use of online communities are outlined, as well as the role of such communities in everyday life. Usage and observation strategies are characterised by the fact that users are integrated into online communities mainly for treatment information and counselling, while for representatives of the communication strategy the communicative component is the most important, serving to discuss a variety of issues within rural life, including health, as well as therapeutic communication. This study contributes to the study of the possibilities and limitations of online communities in the context of the lives of older people with chronic illnesses in rural areas.